Manajemen Ekstrakurikuler Olahraga di SMP Darussalam Cimanggu - Rama Cipta Prasetia; Achmad zakaria; Kholidin Kholidin (Pusat Riset dan Inovasi Nasional, 2022)
The benefits of sport are not only about getting a healthy body, but it can also be used as a means of recreation, education, increasing achievement, and even to improve our economic or social status. That wanting to achieve good performance is not easy, it requires a structured, early, tiered and ongoing coaching process with organizational management at the school in order to achieve the desired targets. In general, extracurriculars and management are interrelated so that they can run well and be neatly organized, so schools need to have good management planned from the start, so that they can achieve the desired targets. This research will find out how extracurricular sports are managed at Darussalam Cimanggu Middle School, which includes 3 functions, namely: planning, implementation and evaluation. The research used is quantitative descriptive using non-experimental research methods. The research method uses an instrument in the form of a questionnaire with question items. Student planning results were worth 1222 percentages 86.7%, Principals and Coaches were worth 186 percentages 82.7%. The results of the implementation were 2210 students, the percentage was 85.5%, the implementation of the Principals and Trainers was 152, the percentage was 86.9%. Student evaluation results are worth 1000 percentages 85.1%, Principal and Coach evaluations are worth 116 percentages 77.3%. Based on the data obtained from 52 respondents, the total score was 4886 with a percentage of 85.4%, so it can be said that the extracurricular sports management at Darussalam Cimanggu Middle School has been managed very well.